2016
DOI: 10.1021/acs.molpharmaceut.6b00465
|View full text |Cite
|
Sign up to set email alerts
|

Image-Guided Radiotherapy Targets Macromolecules through Altering the Tumor Microenvironment

Abstract: Current strategies to target tumors with nanomedicines rely on passive delivery via the enhanced permeability and retention effect, leveraging the disorganized tumor microvasculature to promote macromolecule extravasation and the reduced lymphatic and venous drainage that favor retention. Nonetheless, FDA approvals and clinical use of nanomedicines have lagged, reflecting failure to display superiority over conventional formulations. Here, we have exploited image-guided X-irradiation to augment nanoparticle ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 58 publications
1
20
0
1
Order By: Relevance
“…Building on prior work on radiation-induced vascular permeability [47, 48], we recently observed that a single dose of radiation is sufficient to enhance the local extravasation and penetration of circulating macromolecules and nanoparticles, yielding enhanced therapeutic effects of a model nanomedicine [30]. Our prior work established a threshold dose of roughly 5 Gy and demonstrated that radiation’s effects were delayed, with optimal delivery when agents were injected three days after irradiation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Building on prior work on radiation-induced vascular permeability [47, 48], we recently observed that a single dose of radiation is sufficient to enhance the local extravasation and penetration of circulating macromolecules and nanoparticles, yielding enhanced therapeutic effects of a model nanomedicine [30]. Our prior work established a threshold dose of roughly 5 Gy and demonstrated that radiation’s effects were delayed, with optimal delivery when agents were injected three days after irradiation.…”
Section: Discussionmentioning
confidence: 79%
“…Much of the recent interest in radiotherapy has focused on two areas, high-dose, image-guided radiation delivery and strategies to enhance synergy between radiation and immunotherapy. Recently, we observed that a single dose of X-irradiation is sufficient to increase tumor microvascular permeability, leading to higher accumulation of systemically administered macromolecular agents and increased therapeutic effects over delivery by the EPR effect alone [30]. Going farther back, extravasation of serum albumin has long been noted to increase following irradiation [31, 32].…”
Section: Introductionmentioning
confidence: 99%
“…The highest absorbed dose was measured for protocol 5 (about 700 mGy) and the lowest was measured for protocol 2 (about 4 mGy). Although these values are well below therapeutic thresholds for rodents x-ray irradiation (typically > 6 Gy), the appearance of chromosomal aberrations in mammals has been reported with doses of 250-300 mGy [28][29][30].…”
Section: Discussionmentioning
confidence: 90%
“…Size is one of the most important parameters influencing the in vivo biodistribution of nanocarriers and has a great impact on the mode of cellular internalization (Petros and DeSimone, 2010). Nanocarriers with the size of 20-100 nm are considered best suitable for enhanced permeability and retention (EPR) effect (Svenson, 2016), while avoiding extravasation from normal blood vessels which occurs only with particles below 10 nm (Appelbe et al, 2016). This also avoids removal from the body through renal clearance for particles below 5 nm or elimination by the reticuloendothelial system (RES) which traps particles above 100 nm (Liu et al, 2016).…”
Section: Preparation Of Apoferritin-bound Ellipticine (Apoelli) Nanopmentioning
confidence: 99%